1975
DOI: 10.1021/bi00678a032
|View full text |Cite
|
Sign up to set email alerts
|

5-Methyl-5,6,7,8-tetrahydropteroyl oligo-γ-L-glutamates. Synthesis and kinetic studies with methionine synthetase from bovine brain

Abstract: The synthesis of 5-methyl-5,6,7,8-tetrahydropteroly tri-, pena-, and heptaglutamate has been accomplished by reductive methylation of the tetrahydropteroyl oligoglutamate with formaldehyde, followed by purification on DEAE-Sephadex. The corresponding [5-14-C]methyltetrahydropteroyl oligoglutamates were prepared from 14-CH-2-0, and tested as substrates for methionine synthetase (EC 2.1.1.13) ISOLATED FROM BOVINE BRAIN. In all cases, the polyglutamate conjugates were better substrates (lower Km, higher Vmax) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Formation of Uro III at a lower concentration of tetrahydropteroylheptaglutamate suggests that polyglutamated folates may be more efficient coenzymes for the synthesis of uroporphyrinogen. These results are not unexpected, since it has been reported that polyglutamated folates function as preferred coenzyme forms for the enzymes methionine synthetase (EC 2.1.1.13), thymidylate synthase (EC 2.1.1.45) and 10-formyltetrahydrofolate :5' -phosphoribosyl -5 -aminoimidazol-4-ylcarboxamide formyltransferase (EC 2.1.2.3) (Coward et al, 1975;Dolnick & Cheng, 1978;Baggott & Krumdieck, 1979;Kisliuk et al, 1981).…”
Section: Discussionmentioning
confidence: 59%
“…Formation of Uro III at a lower concentration of tetrahydropteroylheptaglutamate suggests that polyglutamated folates may be more efficient coenzymes for the synthesis of uroporphyrinogen. These results are not unexpected, since it has been reported that polyglutamated folates function as preferred coenzyme forms for the enzymes methionine synthetase (EC 2.1.1.13), thymidylate synthase (EC 2.1.1.45) and 10-formyltetrahydrofolate :5' -phosphoribosyl -5 -aminoimidazol-4-ylcarboxamide formyltransferase (EC 2.1.2.3) (Coward et al, 1975;Dolnick & Cheng, 1978;Baggott & Krumdieck, 1979;Kisliuk et al, 1981).…”
Section: Discussionmentioning
confidence: 59%
“…As shown in Scheme I, only two enzymes catalyze reactions involving CH3-H4PteGIul in mammalian cells, namely methylenetetrahydrofolate reductase and cobalamin-dependent methionine synthase (EC 2.1.1.13). Both these enzymes show higher affinity for polyglutamate than for monoglutamate substrates (13,24, and data presented below). The metabolism of CH3-H4PteGIu~ can be impaired by treatment of animals with N20, which inhibits methionine synthase and leads to secondary declines in the cellular levels of methionine and AdoMet.…”
Section: Incorporation Of Plasma Folate Derivatives Into the Cellularmentioning
confidence: 99%
“…In mammalian cells, especially in hepatocytes and erythrocytes, folate is stored in the form of polyglutamate derivatives. These compounds, with four to seven glutamates bound in y-linkage to the glutamate moiety of the folate, are as effective as the monoglutamates in enzymatic reactions involving reduced folates (Coward et al 1974(Coward et al & 1975. Like physiological folates, MTX can be converted intracellularly to polyglutamates (Hendel 1978; Kamen et al 1981;da Costa & Iqbal 198 I), hereby competing for the enzyme pteroylglutamyl conjugase, which results in a decrease in the synthesis of pteroylpolyglutamates, and eventually in reduced total intracellular folate storage (Brown et al 1974).…”
Section: Discussionmentioning
confidence: 99%